The Role of Economic and Financial Crime Commission (EFCC) in Combating Corruption in Nigeria - Matthew Funsho Bello; Adaran Olapade Cosmas (Musamus Journal of Public Administration, 2022)
Corruption as a â€œmonsterâ€ subverts public institutions and their capacity to perform their assigned tasks efficiently, thereby damaging the substantive interest and endangering the lives of citizens whom these institutions are meant to serve. This indicates that the higher the propensity and will of the state to combat corruption the lower the dangers underdevelopment and societal disintegration, and vice-versa. The main objective of the study is to assess the role of the Economic and Financial Crimes Commission in combating corruption. The secondary source of data collection was used for this study. The study revealed that political interference hinders the EFCC from performing its role in the fight against corruption. Also, the study also found out that the EFCC has played a role in reducing the level of corruption in the public sector. It was recommended that the federal government should be committed to the sincere translation of the expressed political will of fighting corruption into reality by allowing the anti-corruption institutions to operate without political intervention in order not to compromise with their statutorily assigned responsibilities